Physiological methods as indexes of listening effort measurement: an integrative literature review - Guijo, Laura Mochiatti; Cardoso, Ana Cláudia Vieira (ABRAMO Associação Brasileira de Motricidade Orofacial, 2018)
ABSTRACTPurpose: to review the scientific literature and present existing instruments and methods for the objective assessment of the listening effort in normal hearing individuals worldwide.Methods: a literature integrative review whose purpose was to gather and summarize the scientific knowledge regarding the objective methods theme for measuring the listening effort, developed through the search of articles in specialized national and international journals, in the English and Portuguese languages, available in the databases: PUBMED, Cochrane Library, LILACS and SCIELO.Results: 18 articles which used physiological methods to measure the listening effort in individuals with normal hearing were reviewed. The main findings described in those articles refer to the author(s) and purpose(s) of the research, country where the research was conducted, casuistry, physiological method used and results.Conclusion: there is no consensus among the researchers about the best physiological method to measure this parameter, that is, this effort in the speech perception tasks, although the level of skin conductance is considered the most accurate measure to date.

RESUMOObjetivo: revisar a literatura científica e apresentar os instrumentos e métodos existentes para a avaliação objetiva do esforço auditivo em indivíduos normo-ouvintes no cenário mundial.Métodos: esta foi uma revisão integrativa de literatura cujo intuito foi reunir e resumir o conhecimento científico a respeito da temática métodos objetivos para mensuração do esforço auditivo, desenvolvida por meio da busca de artigos em periódicos especializados, nacionais e internacionais, nos idiomas inglês e português, disponíveis nas bases de dados: PUBMED, Biblioteca Cochrane, LILACS e SCIELO.Resultados: foram revisados 18 artigos nos quais os métodos fisiológicos foram empregados para mensurar o esforço auditivo em indivíduos normo-ouvintes. Os principais achados dos artigos revisados se referem aos autore(s) e objetivo(s) da pesquisa, país onde a pesquisa foi conduzida, casuística, método fisiológico empregado e, resultados.Conclusão: não existe consenso entre os pesquisadores quanto ao melhor método fisiológico para mensurar este parâmetro, ou seja, este esforço nas tarefas de percepção de fala, embora o nível de condutância da pele tenha sido considerado a medida mais precisa até o momento.
Métodos fisiológicos como índices de mensuração do esforço auditivo: uma revisão integrativa da literatura
Keywords: Hearing; Cognition; Heart Rate; Pupil; Galvanic Skin Response; Audição; Cognição; Frequência Cardíaca; Pupila; Resposta Galvânica da Pele